The Evolution of Scientific Literacy Research in Science Education: A Bibliometric Analysis of Trends, Themes, and Collaboration (2016-2025) - Ahmad Saputra; Insih Wilujeng; Antuni Wiyarsi (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to map the development of scientific literacy research within the field of science education by examining publication trends, influential contributors, thematic structures, and collaboration patterns based on Scopus-indexed literature published between 2016 and 2025. Methodology: A bibliometric analysis was conducted using the Scopus database. Relevant journal and review articles were retrieved using the keywords “scientific literacy” and “science education.” Bibliographic data were analyzed and visualized using the Bibliometrix package (R software) to examine publication growth, source impact, thematic evolution, and collaboration networks. Main Findings: The results reveal a steady increase in research output on scientific literacy in science education over the past decade, with contributions concentrated among a limited number of authors, journals, institutions, and countries. Core research themes include scientific literacy, science education, and nature of science, while emerging topics such as misinformation, climate literacy, digital literacy, and citizenship have gained prominence in recent years. Collaboration patterns indicate stable yet selective networks at both author and country levels. Novelty/Originality of this study: This study provides a comprehensive decade-long bibliometric mapping that integrates trends, contributor impact, thematic structures, and collaboration patterns in scientific literacy research within science education. The findings offer an updated multidimensional overview of the field, support clearer positioning of future research agendas, and highlight underexplored themes and opportunities for broader international collaboration.